High birth prevalence of sickle cell disease in Northwestern Tanzania. Issue 1 (2nd August 2017) - Ambrose, Emmanuela E.; Makani, Julie; Chami, Neema; Masoza, Tulla; Kabyemera, Rogatus; Peck, Robert N.; Kamugisha, Erasmus; Manjurano, Alphaxard; Kayange, Neema; Smart, Luke R.
Abstract: Background: Worldwide, hemoglobinopathies affect millions of children. Identification of hemoglobin disorders in most sub‐Saharan African countries is delayed until clinical signs of the disease are present. Limited studies have been conducted to understand their prevalence and clinical presentation among newborns in resource‐limited settings. Methodology: This was a prospective cohort study. Newborns (aged 0–7 days) at two hospitals in Northwestern Tanzania were enrolled and followed prospectively for 6 months. Clinical and laboratory information were collected at baseline. Participants were screened for hemoglobinopathies using high‐performance liquid chromatography. Clinical and laboratory follow‐up was performed at 3 and 6 months for those with hemoglobinopathies as well as a comparison group of participants without hemoglobinopathies. Results: A total of 919 newborns were enrolled. Among these, 1.4% (13/919) had sickle cell anemia or Hb S/β 0 ‐thalassemia (Hb FS), and 19.7% (181/919) had sickle cell trait or Hb S/β + thalassemia (Hb FAS). Furthermore, 0.2% (two of 919) had β + ‐thalassemia. Red cell indices compared between Hb FS, Hb FAS, and Hb FA were similar at baseline, but hemoglobin was lower and red cell distribution width was higher in children with Hb FS at 3‐ and 6‐month follow‐up. Febrile episodes were more common for children with Hb FS at 3‐ and 6‐month follow‐up. Conclusion: The prevalence of sickle cell disease among neonates born in Northwestern Tanzania is one of the highest in the world. Newborn screening is needed early in life to identify neonates with hemoglobinopathies so that clinical management may commence and morbidity and mortality related to hemoglobinopathies be reduced.